TREX1 is expressed by microglia in normal human brain and increases in regions affected by ischemia - Kothari, Parul H.; Kolar, Grant R.; Jen, Joanna C.; Hajj‐Ali, Rula; Bertram, Paula; Schmidt, Robert E.; Atkinson, John P. (Brain pathology (Zurich, Switzerland), 2018)
Background Mutations in the three‐prime repair exonuclease 1 (TREX1) gene have been associated with neurological diseases, including Retinal Vasculopathy with Cerebral Leukoencephalopathy (RVCL). However, the endogenous expression of TREX1 in human brain has not been studied. Methods We produced a rabbit polyclonal antibody (pAb) to TREX1 to characterize TREX1 by Western blotting (WB) of cell lysates from normal controls and subjects carrying an RVCL frame‐shift mutation. Dual staining was performed to determine cell types expressing TREX1 in human brain tissue. TREX1 distribution in human brain was further evaluated by immunohistochemical analyses of formalin‐fixed, paraffin‐embedded samples from normal controls and patients with RVCL and ischemic stroke. Results After validating the specificity of our anti‐TREX1 rabbit pAb, WB analysis was utilized to detect the endogenous wild‐type and frame‐shift mutant of TREX1 in cell lysates. Dual staining in human brain tissues from patients with RVCL and normal controls localized TREX1 to a subset of microglia and macrophages. Quantification of immunohistochemical staining of the cerebral cortex revealed that TREX1+ microglia were primarily in the gray matter of normal controls (22.7 ± 5.1% and 5.5 ± 1.9% of Iba1+ microglia in gray and white matter, respectively) and commonly in association with the microvasculature. In contrast, in subjects with RVCL, the TREX1+ microglia were predominantly located in the white matter of normal appearing cerebral cortex (11.8 ± 3.1% and 38.9 ± 5.8% of Iba1+ microglia in gray and white matter, respectively). The number of TREX1+ microglia was increased in ischemic brain lesions in central nervous system of RVCL and stroke patients. Conclusions TREX1 is expressed by a subset of microglia in normal human brain, often in close proximity to the microvasculature, and increases in the setting of ischemic lesions. These findings suggest a role for TREX1+ microglia in vessel homeostasis and response to ischemic injury.